Life skills activities for secondary students with special needs - Mannix, Darlene. (Center for Applied Research in Education, 1995)
Interpersonal skills. Communication skills. Academic and school skills. Practical living skills. Vocational skills. Lifestyle choices. Problem-solving skills.